PENGARUH SOSIALISASI PAJAK, PEMAHAMAN AKUNTANSI, DAN TINGKAT PENDAPATAN TERHADAP KEPATUHAN WAJIB PAJAK SEKTOR UMKM - Fauzan Zharfan Syah Iskandar; Erlina Herowati (Jurnal Akuntansi Dan Manajemen, 2022)
The existence of MSMEs is one of the most important parts of the Indonesian economy, especially income tax from businesses received. The essence of the existence of taxes as a solution to the limitations of development funds from a government that has the main goal of improving the welfare of the community. This study aims to analyze how tax incentives, tax knowledge, tax socialization, accounting understanding, and income levels fulfill their tax obligations. This study uses quantitative data with primary data sources obtained through online questionnaires in the form of Google Forms. The sample in this study used a purposive sampling method with as many as 50 MSME taxpayers located throughout the Special Region of Yogyakarta. Data processing using SPSS. The tests conducted in this study consisted of descriptive statistical analysis, data quality test, classical assumption test, multiple regression analysis, coefficient of determination test, F test, and t-test. The results of this study indicate that tax incentives, accounting understanding, and income levels have a positive effect on MSME taxpayer tax compliance. Meanwhile, tax knowledge and tax socialization have a negative effect on MSME taxpayer tax compliance.